Nanosilica-modified binder in porous asphalt under varied ageing conditions - Khairil Azman, Masri; Putra Jaya, Ramadhansyah; Ahmad Kamil, Arshad; Mohamad Saifullah, Samsudin; Mohd Rosli, Mohd Hasan (Springer, 2025)
Porous asphalt (PA) is a road surfacing layer with open-graded gradation that contained high percentage of interconnected air voids. In Malaysia, the performance of PA may affected by the high temperatures and increasing traffic volume. This study uitilised colloidal nanosilica (NS) as the additive. The purpose of this study is to improve the PA resistance to overcompaction and stiffness performance by using NS-modified binders to manufacture superior and more durable PA (NS-MB). The physical properties of the NS-modified asphalt binders were evaluated through various tests, including penetration, softening point, rotational viscosity, temperature susceptibility, ductility, and storage stability tests, rheological tests with the Dynamic Shear Rheometer, and overcompaction resistance using the Asphalt Pavement Analyzer. The results indicated that NS-MB and NS-PA could enhance PA performance over various temperatures and stresses. Various tests were conducted to investigate the potential of NS as a modified asphalt binder for enhancing the asphalt mixture. The tests included evaluated for permeability, binder draindown, Cantabro loss, robust modulus, dynamic creep, and rust resistance of the asphalt mixture. The Cantabro test results revealed that the inclusion of nanosilica increased the abrasion resistance of PA. The inclusion of NS can increase PA's overall performance. A statistical model was developed to establish a connection between the rut depth of PA and the properties of asphalt binder.